Modeling the Effects of Targeted Mass Media Campaigns on Alcohol Abuse in Kenya - G. G. Muthuri; D. M. Malonza; F. Nyabadza (International Journal of Mathematics And its Applications, 2019)
Alcoholism causes serious harmful effects to the addicts and the whole community in general. The mass media campaign against alcohol acts as a source of information to halt alcohol abuse and its potentially harmful effects. We developed a deterministic model for alcohol abuse considering the influence of pre-exposure of mass media campaigns against alcohol abuse. We analyzed the local and global stability of the AFE and the endemic equilibrium point of the model. The nature of the bifurcation of the model was analyzed using Center Manifold Theorem. Numerical simulations were carried out to determine where the campaigns should be targeted for effective control of the abuse. The results showed that mass media campaigns against alcohol consumption reduce alcohol abuse in the community. The model was validated using data from rehabilitation centers in Kenya. The results to policymakers imply that the mass media campaign should be regulated to reduce alcohol addiction.